Readiness towards digitalization among auditors in Malaysian financial institution - Anbarasan, Kumar (2024)
This study investigates the readiness of auditors in Malaysian financial institutions to embrace digitalization. It examines the influence of organizational support, technology benefits, and people's emotions on auditors' readiness for digital transformation. Through qualitative research involving semi-structured interviews, the study identifies key factors shaping auditors' readiness and proposes a conceptual framework to guide future research and practice. The findings reveal that continuous training programs, investment in advanced technologies, and a supportive management team are crucial for fostering readiness among auditors. The integration of digital technologies, such as data analytics, artificial intelligence, and cloud computing, into audit processes could improve efficiency, accuracy, and the ability to focus on more strategic tasks. Auditors expressed optimism, positivity, excitement, and confidence about the increasing reliance on digital technologies in their profession. The study concludes that organizational support, technology benefits, and people's emotions are vital in shaping auditors' readiness towards digitalization.